Analisis Teks Meme Bertema Virus Corana dalam Unggahan di Twitter (Suatu Pendekatan Multimodal) - Oktariyani; Eva Nurchurifiani; Ratna Said (LPPM STKIP PGRI Bandar Lampung, 2022)
This study aims to critically analyze the Corona Virus-themed meme text which is analyzed based on a multimodal theory review, which includes (1) lexical analysis, (2) visual analysis, and (3) inter-mode relations. The analytical method used is the multimodal theory of Kress-Leuween. In a multimodal analysis of @edwin_basuki's twitter upload in the corona virus discourse, persuasive sentences were found that aim to entice readers. to stay healthy and follow the government's instructions to stay at home. Based on the findings and discussion of the research, it was found in @edwin_basuki's twitter upload using lexical, and visual, in forming meaning for certain purposes and interests. These relations consist of lexical relations, namely participants. Then the visual relation consists of participant, iconography, gaze, composition, setting, distance, salience, modality, and framing.